Comparison of the Effectiveness of Pregnancy Exercises and Prenatal Yoga on Reducing Back Pain in Pregnant Women at the Majenang II Health Center Cilacap Regency - Wulandara, Qanita; Lisa Yulianti; Sri Gustini (Sultan Agung Islamic University of Semarang, 2025)
Back pain is one of the most common discomforts that occurs in pregnant women during pregnancy which begins to be felt when pregnancy enters the second trimester and will increase as the pregnancy progresses. To relieve low back pain that is felt by pregnant women is exercise. Pregnancy gymnastics and Prenatal Yoga are a form of exercise that can be done by pregnant women. This study aims to analyze the comparison of the effectiveness between Pregnancy Gymnastics and Prenatal Yoga on the Reduction of Back Pain in Pregnant Women at the Majenang II Health Center, Cilacap Regency. This study uses the research design used in this study is a Quasy Experiment research design using the equivalent time sample design model, which is a research design consisting of two groups of samples that are equivalent in time. Sample A was given the X1 treatment and the B sample was given the X2 treatment. The sampling technique used was purposive sampling so that a sample of 50 respondents was obtained. The results of this study showed that there was an effect of pregnancy exercises and prenatal yoga on reducing back pain in pregnant women at the Majenang II Health Center, Cilacap Regency with a p value of 0.000 smaller than alpha 0.05 each